The role of internal control and financial audit in implementing European financed projects from European social fund category - NICA, Dumitru; COCOȘATU, Cristinel-Claudiu; TOMOIAGĂ, Liviu (Annals of Spiru Haret University. Economic Series, 2012)
In the beginning we have discussed the role of internal control in implementing European financed projects by the European Social Fund, type POSDRU and PODCA. The paper continues by emphasizing the main requirements presented in ISRS 4400 entitled “Missions based on agreed-upon procedures regarding financial data” for the auditing of ESF financed programs. Later on, we have focused on some defining criteria incorporated in CAFR guides and resolutions for POSDRU type European projects according to the European Directives standards. Furthermore we have analyzed some requirements mentioned in the Beneficiary Manual elaborated by AMPOSDRU and AMPODCA in relation to the audit for POSDRU and PODCA type projects. In the end, we have presented the conclusions and suggestions we have come along as a result of our research.